If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 5 = x + -12 Reorder the terms: 5 + -2x = x + -12 Reorder the terms: 5 + -2x = -12 + x Solving 5 + -2x = -12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + -2x + -1x = -12 + x + -1x Combine like terms: -2x + -1x = -3x 5 + -3x = -12 + x + -1x Combine like terms: x + -1x = 0 5 + -3x = -12 + 0 5 + -3x = -12 Add '-5' to each side of the equation. 5 + -5 + -3x = -12 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = -12 + -5 -3x = -12 + -5 Combine like terms: -12 + -5 = -17 -3x = -17 Divide each side by '-3'. x = 5.666666667 Simplifying x = 5.666666667
| 15-2=15 | | (x^3+4x^2-5x)-(4x^3+x^2-7)= | | -x(-8)-4y=16 | | -4x+9=35 | | 13k+3(k+11)=8k+-7 | | 3y+2=12-y | | 6b-.2=7b | | 5d-27=108 | | 25(C-55)=23750 | | X(2x+1)+4(2x+1)=0 | | 2*(3t^2)*(4t^2-1)=x | | 19+x=14 | | 2k+-2.6=12 | | -6t-8=-7t | | f(x)=3x^3-x^2+5x | | -8g=-9g-2 | | 3p-3=2 | | N-6=2n-16 | | X-.3x=114 | | -9(0)-2y=-20 | | 1.75y^2+2y=0 | | 7n+2=8 | | 22222x+69x=4 | | (x+y-z)(x+y+z)= | | 5y+3=y+1 | | An=(2n^2) | | 5x^3-15x^2+4x-12=0 | | x+(x-2)+2x=82 | | 43+26k=927 | | X^2-12-27=0 | | 8a+5=10 | | x-4=-5x-28 |